The role of the gut-skin axis in the pathogenesis of rosacea - Zielnik, Martyna; Stróżna , Katarzyna; Błażowska, Olga; Jurewicz, Alicja; Gutowska, Oliwia; Nowak, Weronika; Kostuch, Wiktoria; Kowalewski, Łukasz; Styczyńska, Maria; Naziri, Amir (Quality in Sport, 2026)
BACKGROUND AND AIM Rosacea is a chronic inflammatory skin condition affecting the central facial region, characterized by erythema, papulopustules, telangiectasia, and flushing. The aetiology of this disease is multifactorial, involving immune dysregulation, neurovascular instability, and environmental triggers. The aim of this narrative review was to analyze the role of the gut-skin axis in the pathogenesis of rosacea, with particular emphasis on gut microbiota, immune mechanisms, and the potential of dietary and microbiome-targeted therapeutic interventions. MATERIAL AND METHODS A narrative review of current scientific literature was conducted using the MEDLINE (PubMed) database. Original studies, systematic reviews, meta-analyses, and randomized controlled trials published primarily between 2007 and 2025 were included, using search terms including "rosacea," "gut-skin axis," "gut microbiota," "dysbiosis," "SIBO," "Helicobacter pylori," "short-chain fatty acids," "diet," and "probiotics." RESULTS Dysbiosis, reduced SCFA production, and increased intestinal permeability promote systemic inflammation and cutaneous immune activation in rosacea. A significant association between rosacea and gastrointestinal disorders, particularly SIBO and H. pylori infection, was confirmed. SIBO eradication with rifaximin achieved lesion resolution in 78% of rosacea patients. Mediterranean dietary patterns demonstrated protective effects. CONCLUSIONS The gut-skin axis is a significant component of rosacea pathogenesis. Dietary modification, probiotic supplementation, and targeted eradication of SIBO and H. pylori represent promising adjunctive therapeutic strategies. Further randomized controlled trials are required.